Studi Tentang Aktivitas Ekonomi Masyarakat Pesisir Pantai Pelabuhan - Yurial Arief Lubis (Universitas Medan Area, 2014)
This research aims to the shape of economic activities done around the community in Kuala Langsa Ports. This research was conducted in the village of Kuala Langsa by taking a sample of 30% of the total population (159 families) are directly related to the economic activity of the port of Kuala Langsa. Data collection techniques used is indirect communication, in the form of questionnaires and documentation. Furthermore, the data obtained in the qualitative descriptive analysis. The results showed that (1) There are five (5) Economic Activity form communities do in Port of Kuala Langsa namely Fishermen, port workers 14 23.73%, 8.47% Employees harbor, 16.95% and 8.47 Trader % nautical travel services provider, 76.27% of them claimed to have a sideline to boost economic activity pendapaatan. Then 18.64% of the people have an average income per month exceeds UMP Nanggroe Aceh Darussalam, while 81.36% is below the UMP Aceh or are classified as poor. (2) Of the five forms of economic activity that is done, when seen an increase in the average income before and after switching livelihood, there are 3 groups of economic activity that have increased the average income of the port employees, vendors and service providers of marine tourism and two groups of activity other economic decline average income.